Highly porous graphitic biomass carbon as advanced electrode materials for supercapacitors. Issue 17 (11th August 2017) - Gong, Youning; Li, Delong; Luo, Chengzhi; Fu, Qiang; Pan, Chunxu
Abstract : 3D porous graphitic biomass carbon as advanced supercapacitor electrode materials synthesized by a low-cost and effective one-step method. Abstract : In this work, we established a one-step strategy to synthesize three-dimensional porous graphitic biomass carbon (PGBC) from bamboo char (BC), and studied its electrochemical performance as electrode materials for supercapacitors. Using potassium ferrate (K2 FeO4 ) to fulfil the synchronous carbonization and graphitization of bamboo carbon, this method is less time-demanding, highly efficient and pollution-free, when compared with a conventional two-step strategy. The as-prepared PGBC sample possessed a porous structure with a large specific surface area (1732 m 2 g −1 ) and abundant micropores, as well as a high graphitization degree demonstrated by XRD and Raman. Further electrochemical measurements revealed that the PGBC electrode exhibited a high specific capacitance of 222.0 F g −1 at 0.5 A g −1, and the solid-state symmetric supercapacitor in an aqueous electrolyte (KOH/PVA) presented considerable synergetic energy–power output properties with an energy density of 6.68 W h kg −1 at a power density of 100.2 W kg −1, and 3.33 W h kg −1 at 10 kW kg −1 . Moreover, the coin-type symmetric supercapacitor in an ionic liquid electrolyte (EMIM TFSI) delivered a higher energy density of 20.6 W h kg −1 at a power density of 12 kW kg −1 . This approach holds great promise to achieve low-cost, green and industrial-grade production of renewable biomass-derived carbon materials for advanced energy storage applications in the future.